Characterization of Enriched Meat-Based Pâté Manufactured with Oleogels as Fat Substitutes - Artur J. Martins; José M. Lorenzo; Daniel Franco; Mirian Pateiro; Rubén Domínguez; Paulo E. S. Munekata; Lorenzo M. Pastrana; António A. Vicente; Rosiane L. Cunha; Miguel A. Cerqueira (Gels, 2020)
Nowadays, one of the strongest factors affecting consumers’ choice at the moment of purchasing food products is their nutritional features. The population is increasingly aware of the diet–health relationship and they are opting for a healthy lifestyle. Concerns with the increasing number of heart-related diseases, which are associated to the consumption of fats, are placing the functional food market in a relevant growth position. Considering that, our goal was to develop, under semi-industrial processing conditions, a healthy meat-based spreadable product (pâté) with reduced fat content through replacement of pork fat by healthier structured oil. Beeswax was used to develop an edible oleogel based on linseed oil with a high content of linolenic acid. A decrease of the hardness and adhesivity was verified for pâtés with oleogel incorporation. Linseed oil inclusion was the main factor leading to an increase of polyunsaturated fatty acids (PUFA) content in pâté samples. A decrease up to 90% in the n-6/n-3 (omega-6/omega-3) ratio can signify a better nutritional value of the obtained pâté samples, which can result in a possible upsurge in omega-3 bioavailability through digestion of these pâtés. This could be an interesting option for the consumption of n-3 polyunsaturated fatty acids, targeting, for example, the reduction of cardiovascular diseases.